Kinetics of chemical bath deposition of zinc sulfide ZnS - A. A. Uritskaya; N. S. Kozhevnikova; T. V. Yakubova (Chimica Techno Acta)
The paper is devoted to kinetic methods of chemical bath deposition of zinc sulfide ZnS from aqueous alkaline solutions containing ehylenediamine complex zinc salt Zn(En)n2+ and diamide of thiocarbonic acid N2H4CS. It is established that the rate of formation of ZnS is weakly dependent on pH, depends on the concentration of the precipitant ((N2H4CS) and decreases with increasing concentration of ligand (ethylenediamine). The calculation of the theoretical curves on the experimentally obtained kinetic equation shows a satisfactory description of experimental data that allows to recommend it to calculate the rate of formation of ZnS in aqueous alkaline solutions of N2H4CS.